2010 International Conference on Indoor Positioning and Indoor Navigation 2010
DOI: 10.1109/ipin.2010.5646207
|View full text |Cite
|
Sign up to set email alerts
|

Wi-Fi positioning: System considerations and device calibration

Abstract: Due to an increasing number of public and private access points in indoor and urban environments, Wi-Fi positioning becomes more and more attractive for pedestrian navigation. In the last ten years different approaches and solutions have been developed. But Wi-Fi hardware and network protocols have not been designed for positioning. Therefore, Wi-Fi devices have different hardware characteristics that lead to different positioning accuracies. In this article we analyze and discuss hardware characteristics of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Haeberlen et al [17] proposed the use of linear mapping for transforming signal strength samples from one device to match the ones of another device, however Park et al [18] claim that linear transformation alone does not solve the problem and therefore they combine it with a Kernel estimation using a wide Kernel width to further reduce the positioning error. In [37], Vaupel et al carry out anechoic chamber measurements to obtain the signal strength offsets between different devices and then apply those offsets to calibrate the radiomap according to the device used. This assumes the availability of an anechoic chamber and it limits the applicability of this approach.…”
Section: Device Heterogeneity In Fingerprint Positioningmentioning
confidence: 99%
“…Haeberlen et al [17] proposed the use of linear mapping for transforming signal strength samples from one device to match the ones of another device, however Park et al [18] claim that linear transformation alone does not solve the problem and therefore they combine it with a Kernel estimation using a wide Kernel width to further reduce the positioning error. In [37], Vaupel et al carry out anechoic chamber measurements to obtain the signal strength offsets between different devices and then apply those offsets to calibrate the radiomap according to the device used. This assumes the availability of an anechoic chamber and it limits the applicability of this approach.…”
Section: Device Heterogeneity In Fingerprint Positioningmentioning
confidence: 99%
“…A common assumption about the RSSI coming from multiple APs is that the signals are distributed as multivariate Gaussians. It has however been reported (di Flora and Hermersdorf, 2008;Vauper et al, 2010) that this is not always the case: the signal can be multimodal, different recording devices can measure quite different distributions at the same location and simple changes in antenna orientation can impact the RSSI by 10dBm (Curran et al, 2011). In their experiments, Mirowski et al (2011) reported that the RSSI of an immobile receptor can be distributed in a bimodal way and that they oscillate between two extreme values distant by as much as 10dB (see Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…For instance Ultra Wide Band (UWB) is broadly used for medical applications because it allows to reach even millimetre accuracy (Mahfouz et al, 2008), while other magnetic-based systems allow to reach decimetre level positioning accuracy (Storms et al, 2010). Distances between object and source could be of 0-15 m. Radio Frequency Identification (RFID) (Zhou and Liu, 2007) or Wi-Fi (Vaupel et al, 2010) can potentially provide high accuracy resolutions too, but that accuracy is highly dependent on the number and the spacing among the installed tags. The same considerations can be extended also to the methods based on fingerprints approaches too.…”
Section: Introductionmentioning
confidence: 99%